2014
DOI: 10.1111/tme.12103
|View full text |Cite
|
Sign up to set email alerts
|

The use of therapeutic apheresis in cardiovascular disease

Abstract: In the last few years, therapeutic apheresis (TA) has emerged as a valuable treatment option for certain life-threatening cardiovascular diseases (CVDs) and for all the cardiac dysfunctions caused by autoimmune or metabolic disorders. Besides the well-established indications for apheresis treatment, such as familial hypercholesterolaemia, hyperviscosity syndrome and thrombotic thrombocytopenic purpura (TTP), we discuss the novel approaches in the therapy of dilated cardiomyopathy, cardiac failure and some spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
(144 reference statements)
0
3
0
Order By: Relevance
“…Ascorbate administration can be useful to lower the levels of hydrogen peroxide and proinflammatory mediators in patients undergoing apheresis (45). It was also initially hypothesized that ascorbic acid may decrease lipoprotein(a) concentrations; however, a study in 100 healthy people did not confirm this hypothesis (46).…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbate administration can be useful to lower the levels of hydrogen peroxide and proinflammatory mediators in patients undergoing apheresis (45). It was also initially hypothesized that ascorbic acid may decrease lipoprotein(a) concentrations; however, a study in 100 healthy people did not confirm this hypothesis (46).…”
Section: Discussionmentioning
confidence: 99%
“…7 8 It is also being studied as a novel therapy in patients with dilated cardiomyopathy. 9 There is controversial evidence about the effect of plasmapheresis on donor's hypercoagulability. This procoagulant effect was studied in 54 donors and it was found that in comparison to pre-plasmapheresis sample, post-plasmapheresis sample showed significant reduction of PT, increased clot growth velocity and increased endogenous thrombin generation turning normocoagulant plasma into a hypercoagulant one.…”
Section: Case Reportmentioning
confidence: 99%
“…In this issue we have two interesting reviews. One is from Professor Claudio Napoli and colleagues explaining how therapeutic apheresis, widely provided by transfusion medicine services, is an important tool in the management of patients with cardiac disease, not only for thrombotic thrombocytopenic purpura, but also for immune disorders affecting the heart and hyperlipidaemias (Pignalosa et al , ). Further expansion of these therapeutic services seems likely as technical improvements and additional tools and expertise enhance its application and reach.…”
mentioning
confidence: 99%